광학부 중앙 원공을 가지는 안내렌즈삽입술 후 발생한 색소분산증후군 및 역 동공 차단 - 이수찬(Su Chan Lee), 정혜진(Hye Jin Chung), 정윤석(Yun Suk Chung), 최진영(Jin Young Choi), 최기용(Kee Yong Choi), 김미정(Mi Jeung Kim) (Daihan angwa haghoi jabji, 2016)
목적: 광학부 중앙 원공이 있는 안내렌즈(AQUA ICLⓇ) 삽입술을 시행 받은 환자에서 발생한 색소분산증후군과 역 동공 차단이 안내렌즈 제거 및 주변부 레이저 홍채절개술 후 호전된 증례를 보고하고자 한다. 증례요약: 양안 근시 소견을 보이는 29세 여자 환자에게 양안 AQUA ICLⓇ 삽입술을 시행하였다. 삽입술 후 4주에 양안 모두 색소분산이 발생하면서 안압이 각각 34 mmHg로 증가하였으며 최대 약물치료에도 불구하고 안압이 조절되지 않아 삽입술 후 8주에 안내렌즈를 제거하였다. 안내렌즈 제거 직후 색소 분산이 감소하면서 안압이 조절되는 양상을 보였으나 제거 수술 4주에, 우안 홍채의 후방이동 및 역 동공 차단이 발생하며 우안 안압이 46 mmHg로 다시 증가하였다. 우안에 주변부 레이저 홍채절개술을 시행한 후 역 동공 차단이 해소되면서 색소 분산이 감소되었고 우안 안압이 13 mmHg로 정상화되었다. 2주 후 좌안에 예방적 레이저 홍채절개술을 시행하였다. 좌안 레이저 홍채절개술 시행 4주 후, 양안에 선택적 레이저 섬유주성형술을 시행하였으며 4주 후 측정 안압은 점안안압하강제를 투약하는 상태에서 우안 11 mmHg, 좌안 12 mmHg로 측정되었다. 결론: 광학부 중앙 원공을 가지는 안내렌즈 삽입술 후 조기에 색소분산증후군이 발생할 수 있으며, 색소분산증후군이 안내렌즈 제거 후에도 지속되면서 역 동공 차단이 동반될 경우 주변부 레이저 홍채절개술이 부분적으로 효과가 있음을 알 수 있었다. Purpose: To report a case of pigment dispersion syndrome and reverse pupillary block secondary to the implantation of implantable collamer lens (ICL) with a central hole (AQUA ICL®) that was treated with ICL removal and laser peripheral iridotomy (LPI). Case summary: A 29-year-old woman with myopia in both eyes underwent implantation of AQUA ICL®. Four weeks postoperatively, the intraocular pressure (IOP) increased to 34 mm Hg and the patient showed pigment dispersion syndrome in both eyes. Since the IOP did not reduce with the maximum tolerable medical therapy, the ICLs were removed 8 weeks after implantation. The pigment dispersion subsided and IOP reduced shortly after ICL removal. However, 4 weeks after removal of ICL, posterior iris bowing and reverse pupillary block occurred in the right eye and the IOP increased to 46 mm Hg. LPI was performed in the right eye, and the reverse pupillary block was dissolved after a reduction in pigment dispersion. The IOP subsequently normalized to 13 mm Hg. Two weeks later, prophylactic LPI was performed in the left eye. Four weeks after prophylactic LPI, selective laser trabeculoplasty was performed on both eyes. As a result, the IOP was 11 mm Hg in the right eye and 12 mm Hg in the left eye after 4 weeks of treatment with topical IOP-lowering medications. Conclusions: The present case indicates that implantation of ICL with a central hole can lead to early postoperative pigment dispersion syndrome. When this condition persists and is accompanied by reverse pupillary block after ICL removal, LPI can be partially effective. KCI Citation Count: 0